INFLUENCE KNOWLEDGE LEVEL FUNDAMENTAL ANALYSIS AND TECHNICAL ANALYSIS ON CONTINUITY OF INVESTING IN SHARIA STOCKS IN SHARIA INVESTMENT GALLERY INDONESIA STOCK EXCHANGE STATE INSTITUTE OF ISLAMIC RELIGION KERINCI - Abi Suar alizar Suar; meirison meirison meirison (Transformatif, 2020)
Once the prospection of sharia trading in the capital market must be supported with a level of knowledge in analyzing the stocks that will be traded. Therefore there is an in-depth knowledge of the analysis of sharia stocks before making transactions on the sharia capital market and needed a deepening of understanding on fundamental and technical analysis to achieve optimal profit in the purchase or sale of Sharia stocks. This research aims to determine the influence of the knowledge level of fundamental analysis in the Continuity of investing in sharia stocks. Influence the level of technical analysis in the continuation of Continuity to invest in sharia stocks and the effect of the knowledge level of fundamental and technical analysis simultaneously on the Continuity of investing in sharia stocks. The research method used in this research is to use a quantitative approach. The result of the study was on a partial (independent) fundamental analysis level (X1) test for the variable Continuity of investing (Y). The influence of Knowledge level technical analysis (X2) partially against the Continuity of investing (Y), both get the result of a  tcount  <  Ttable, OR a significant > 0.05. Zero hypotheses (H0) received, and an alternate hypothesis (HA) is rejected, which means variable X does Not affect the variable Y. Similar results are also obtained From simultaneous calculations (together).